Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set - Page 433: 50


$-3z\sqrt[5] (z^{4})$

Work Step by Step

$\sqrt [5] (-243z^{9})=\sqrt [5] (-243\times z^{5}\times z^{4})$ $=\sqrt [5] (-243)\times \sqrt[5] (z^{5})\times \sqrt[5] (z^{4})=-3z\sqrt[5] (z^{4})$ We know that $\sqrt[5] (-243)=-3$, because $(-3)^{5}=-243$ and also that $\sqrt[5] (z^{5})=z$, because $(z)^{5}=z^{5}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.